Tinjauan Yuridis Tindak Pidana Korupsi Penyalahgunaan Wewenang Dalam Jabatan Di Dinas Pendidikan Nias Selatan (Studi Putusan No. 10/pid.sus.tpk/2017/pn.medan) - Sonya Airini Batubara (Universitas Islam Sumatera Utara, 2019)
Corruption is very closely related to the factor of abuse of authority or influence that exists on someone’s position as an official who deviates from the legal provisions so that the action is detrimental to the economy and state finances. The purpose of writing this study is to find out and to analyze whether in case of the misuse of authority in the Payment of Teacher Professional Allowances, the corruptor has got appropriate punishment by law. The research method used in the writing is normative research that uses a statue approach and conceptual approach.The conclusion of the study is that the application of criminal law both formally and materially in the Corruption Crime of Abuse of Authority by the Treasurer in Decision No.10 / PID.SUS.TPK / 2017 / PN.MEDAN is appropriate, and in terms of the application of material criminal law, the actions of the defendant Maranatha Dachi. SPd. has fulfilled the element of offense as the subsidiary indictment was chosen by the Panel of Judges which states that the Defendant is found guilty of committing Corruption Crime which was regulated in Law No.20 of 2001 concerning Amendment to Law No.31 of 1999 concerning Eradication of Corruption Crimes, and in making decisions against the Corruption of Abuse of Corruption by the Treasurer at the South Nias Education Office Decision No.10 / PID.SUS.TPK / 2017 / PN.MEDAN. The Panel of Judges uses judicial and non-juridical considerations. However, according to the Writer, the judge should dig deeply into the non-juridical considerations primarily concerning matters that incriminate the Defendant.